The meaning of silence in personal communication: spiral of silence or a stimulant of creativity? - Baltezarević, Radoslav Velimir; Kwiatek, Piotr Benon; Baltezarević, Borivoje Velimir; Baltezarević, Vesna Nikola (Creativity Studies, 2022)
Silence is an important part of communication. Depending on the cultural context, silence can be perceived as positive/desirable or as negative/unwelcome. This ambiguity often leads to misunderstandings with other participants in the communication process. The current study discusses the phenomenon of silence and presents the spiral of communication, as a part of nonverbal communication, and refer to the synthesis of silence and creativity. We approach important questions in our study: is silence in communication linked with creativity. If so, through what mechanism? Does the tension in communication affect silence being used as a mode of escaping from a communication process to avoid conflict, tension and uncomfortable situations? Based on the analysis of the theoretical approaches to these phenomena, we empirically test ordinary least squares mediation models based on responses collected from 416 individuals of Serbian nationality. Our study reveals that silence is used to avoid conflict in communication by reducing the feeling of tension. We note that silence does not affect creativity directly. Rather, it has a marginal effect through reducing tension and avoiding conflict and while having opposite opinions.